2021
DOI: 10.3389/fmicb.2021.650991
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Dietary Alteration on the Gut Microbiome and Metabolome of the Rescued Bengal Slow Loris

Abstract: Bengal slow lorises (Nycticebus bengalensis) are threatened by illegal trade. Subsequently, numerous wild-born individuals are rescued and transferred to rescue centers. Metabonomic analysis of intestinal microbiomes has increasingly played a vital role in evaluating the effects of dietary alteration on the captive status of endangered non-human primates. A synthetic analysis was done to test the differences in gut microbes and fecal metabolites between two dietary groups of Bengal slow lorises across 8 weeks.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 44 publications
1
5
0
Order By: Relevance
“…The results indicated that the confiscated animals had stable fiber intake under the current captive diet. It was consistent with the previous study by Ni et al (2021) , which indicated that apple peel and core might significantly contribute to the fiber content for the captive Bengal slow loris.…”
Section: Discussionsupporting
confidence: 93%
“…The results indicated that the confiscated animals had stable fiber intake under the current captive diet. It was consistent with the previous study by Ni et al (2021) , which indicated that apple peel and core might significantly contribute to the fiber content for the captive Bengal slow loris.…”
Section: Discussionsupporting
confidence: 93%
“…Extracted DNA concentration and purity were monitored using a NanoDrop One (Thermo Scientific) and 1% agarose gel electrophoresis. We amplified the hypervariable V3-V4 regions of the 16S rRNA gene using PCR primer set 338F (5′-ACTCCTACGGGAGGCAGCAG-3′) and 806R (5′-GGACTA CHVGGGTWTCTAAT-3′) (Ni et al, 2020). Sequencing libraries were generated using NEBNext® Ultra TM DNA Library Prep Kit for Illumina® (Illumina) following the manufacturer's standards.…”
Section: Dna Extraction and Sequencingmentioning
confidence: 99%
“…The faecal metabolome of black howler monkeys is dominated by lipids, amino acids, carbohydrates and organic acids, similar to other species of nonhuman primates (Garber et al, 2019;Gomez et al, 2015Gomez et al, , 2016Ni et al, 2021). Some of the long-chain fatty acids prominent in the black howler monkey metabolome-palmitic acid, stearic acid and vaccenic acid-are associated with high-fat diets in mice (Daniel et al, 2014) and fruit-dominated diets in lowland gorillas (Gomez et al, 2016).…”
Section: Discussionmentioning
confidence: 87%